Characteristics of Consumers of Family Planning Services in Eastern Nepal - Dahal, Sushma; Subedi, Raj Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2013)
Family planning services in Nepal are provided by government and non-government health facilities. A descriptive cross sectional study was done by secondary data review of eight months from Institutional clinic, District Health Office (DHO) Ilam district. Use of different family planning methods through government health facility was studied in relation to different variables like age, sex, ethnicity, and, number of children. Around 53% of the female users of spacing method and around 47% of female users of permanent method were in age group 20-29 years and 25-29 years respectively. The major reasons for removal of IUCD were husband’s migration and experienced physical problems. Most of the females doing sterilization were from Disadvantaged Janajati group whereas most of the males doing sterilization were from Upper caste ethnic group. Among females doing sterilization, 70% already had their second live birth baby. Out of the total sterilization performed in 8 months, only 15.15% was done among males. So, there is need of increasing male involvement in Family planning. There is also need of programs to encourage spacing methods among the target population. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8482 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 125-138